Ionic cross-linked polymer as well as preparation method and application thereof

By using ionic crosslinking polymers combined with calcium salt and anionic crosslinking agent in the hydrogel, the risk of intestinal obstruction caused by the maintenance of integrity in the small intestine and safety hazards during the preparation process are solved, and the problem of the risk of intestinal obstruction caused by the hydrogel in maintaining integrity in the small intestine is achieved. The effect of efficient swelling in the stomach and dissociation in the intestine improves the safety and compound functionality of the product.

CN119431833APending Publication Date: 2025-02-14XIAMEN TIANCE MATERIAL TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411380105.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Existing hydrogel products maintain high absorption multiples and particle integrity in the small intestine, increasing the risk of diseases such as intestinal obstruction, and long-term stirring and use of flammable solvents, strong acids and other dangerous goods, which poses safety hazards and functions. A single question.

Method used

An ionic crosslinking polymer is used, which is composed of calcium salt and anionic crosslinking agent, and is formed by physical crosslinking between calcium ions and carboxyl groups to provide satiety in the stomach but dissociate in the intestine. The particles reduce the risk of intestinal obstruction and simplify the preparation process through premix and drying of high viscosity raw materials.

Benefits of technology

The effect of efficient swelling in the stomach and dissociation in the intestine is achieved, reducing the risk of intestinal obstruction, simplifying the preparation process, and improving the safety and composite functionality of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005069689290000171
    Figure BDA0005069689290000171
  • Figure BDA0005069689290000191
    Figure BDA0005069689290000191
  • Figure BDA0005069689290000201
    Figure BDA0005069689290000201
Patent Text Reader

Abstract

The invention provides an ionic cross-linked polymer which at least contains a composite cross-linking agent and a water-soluble polymer with a side group containing carboxyl or sodium salt thereof, and the composite cross-linking agent is formed by compounding a calcium salt and an anionic cross-linking agent with a side group containing carboxyl or sodium salt thereof, the ionic cross-linked polymer is formed by cross-linking through physical action between calcium ions and carboxyl, and chemical reaction does not occur among the raw materials. The invention also provides food-grade superabsorbent calcium supplement particles which contain the ionic cross-linked polymer. The food-grade superabsorbent calcium supplement particle can be used as a food additive for providing strong satiety as a main material or an auxiliary material of solid beverages, candies, pet foods, tablets, capsules, electuary and other products, and is widely applied to the fields of foods, medicines and medical instruments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of supramolecular polymers, and in particular to an ion cross-linked polymer and a preparation method thereof, as well as applications in the fields of functional foods, medicines and medical devices. Background Art

[0002] As a new type of product that can provide satiety and assist weight loss, hydrogels have been gradually commercialized and entered the consumer market in recent years. It is known that existing hydrogel products of this type are mainly based on cross-linked sodium carboxymethyl cellulose. Hydrogel products based on cross-linked sodium carboxymethyl cellulose currently have the following main shortcomings:

[0003] First, this type of hydrogel maintains integrity in the stomach and small intestine, and will not be slowly degraded or directly excreted from the body until the colon. For example, CN 105815363 A and CN 112262984 B disclose cross-linked sodium carboxymethyl cellulose chemically cross-linked by citric acid; another example is CN 110740759 A discloses cross-linked sodium carboxymethyl cellulose chemically cross-linked by a multifunctional polyethylene glycol cross-linking agent; another example is CN 110496135B discloses sodium carboxymethyl cellulose chemically cross-linked by citric acid and trivalent metal ions and ion-cross-linked sodium carboxymethyl cellulose, wherein the ionic cross-linking strength formed between the trivalent metal ions and sodium carboxymethyl cellulose is high, and the gel particles do not dissociate in the small intestine environment. These existing technologies, without exception, still maintain a high liquid absorption multiple in the small intestine. Since people's hunger and satiety are mainly perceived by the stomach, the hydrogel also maintains a high liquid absorption multiple and the integrity of the particles in the intestine, which increases the risk of causing diseases such as intestinal obstruction. Therefore, there is a need for a particle that only maintains integrity in the stomach to provide a sense of fullness but dissociates in the intestine, thereby reducing the probability of side effects such as intestinal obstruction and enhancing the safety of the product. Although chitosan-based hydrogels disclosed in CN 113519851 A and CN 115154407 B can maintain integrity in the stomach and dissociate in the intestine, according to the national standard GB 2760-2014 "National Food Safety Standard for the Use of Food Additives", chitosan as a food additive can only be used as a thickener and film-forming agent in Western-style ham (smoked, smoked, and steamed ham) and meat sausages, so the application of such products as food or food additives is very limited.

[0004] Second, this type of hydrogel usually needs to use high-viscosity sodium carboxymethyl cellulose to achieve an ideal swelling effect, and often needs to be fully mixed with a cross-linking agent and other additives in water, and this type of high-viscosity polysaccharide usually needs to be stirred for a long time in water to achieve full dissolution, such as CN 112262984 B needs to be stirred for 24 hours to achieve full dissolution and mixing. At present, the known mixing methods that can improve the mixing efficiency include, such as CN 105815363 A discloses the use of organic solvents, acids, low temperatures and other means for dissolution, and CN 114409929 A discloses the use of solvents such as methanol and ethanol for dissolution. These mixing methods still have some shortcomings. The use of acids and alcohols requires special treatment when blending and removing solvents, otherwise there may be safety hazards such as equipment corrosion, air pollution, fire, and deflagration, and the realization of low temperature requires a special cooling device. Therefore, there is an urgent need for a technical solution that is both safe and harmless and can improve the dissolution efficiency of sodium carboxymethyl cellulose at low cost.

[0005] In addition, the functionality of this type of hydrogel products is often relatively simple, and there are no products with complex functions yet. Summary of the invention

[0006] Against the above background, in order to improve the safety, composite functionality and preparation efficiency of hydrogel products based on sodium carboxymethyl cellulose, the present invention provides an ion cross-linked polymer and a preparation method thereof and its application in food, medicine and medical devices.

[0007] The first aspect of the present invention provides an ion cross-linked polymer, which contains at least a composite cross-linking agent and a water-soluble polymer having a carboxyl group or its sodium salt on the side group, wherein the composite cross-linking agent is a composite of a calcium salt and an anionic cross-linking agent having a carboxyl group or its sodium salt on the side group. The ion cross-linked polymer is cross-linked by the physical action between calcium ions and carboxyl groups, and no chemical reaction occurs between the raw materials.

[0008] In a preferred technical solution of the present invention, the calcium salt is a slightly soluble calcium salt or a calcium salt composition containing the same.

[0009] In a preferred technical solution of the present invention, the calcium salt is a slightly soluble organic calcium salt or a calcium salt composition containing the same.

[0010] In a preferred technical solution of the present invention, the calcium salt is selected from calcium citrate, a combination of calcium citrate and calcium malate, a combination of calcium citrate and a water-soluble calcium salt, a combination of a water-soluble citrate and a water-soluble calcium salt, wherein the water-soluble citrate is selected from sodium citrate, potassium citrate and a combination thereof, and the water-soluble calcium salt is selected from calcium lactate, calcium gluconate, calcium ascorbate and a combination thereof.

[0011] In a preferred technical solution of the present invention, the anionic cross-linking agent is selected from sodium alginate, linseed gum, low-ester pectin and a combination thereof.

[0012] In a preferred technical solution of the present invention, the anionic cross-linking agent is selected from sodium alginate.

[0013] In a preferred technical solution of the present invention, the water-soluble polymer having a carboxyl group or its sodium salt on the side group contains at least 0.5 carboxyl groups per repeating unit on average, and is selected from acrylic acid homopolymers and copolymers thereof, sodium acrylate homopolymers and copolymers thereof, polysaccharide polymers having a carboxyl group or its sodium salt on the side group, and combinations thereof.

[0014] In the preferred technical solution of the present invention, the water-soluble polymer containing a carboxyl group or its sodium salt on the side group is selected from sodium carboxymethyl cellulose, and the viscosity of a 1% aqueous solution prepared from the sodium carboxymethyl cellulose at 25° C. is 50-4000 mPa·s; the degree of substitution of the sodium carboxymethyl cellulose is not less than 0.5.

[0015] In a preferred technical solution of the present invention, the mass ratio of the water-soluble polymer to the anionic crosslinking agent is 1:1-9:1.

[0016] In a preferred technical solution of the present invention, the mass ratio of the anionic crosslinking agent to the calcium ions is 60:1-5:2.

[0017] In a preferred technical solution of the present invention, the molar ratio of the total number of negative charges of acid radical ions of the sparingly soluble organic calcium salt to the total number of positive charges of calcium ions is 9:20-21:20.

[0018] The ion cross-linked polymer has a liquid absorption multiple of not less than 40 times after swelling in a 1 / 10 diluted simulated gastric fluid at pH=2.5 for 1-4 hours.

[0019] In a preferred technical solution of the present invention, the liquid absorption multiple of the ion cross-linked polymer after swelling for 4 hours in 1 / 10 diluted simulated gastric fluid at pH=2.5 varies by no more than ±25% compared with the liquid absorption multiple after swelling for 1 hour.

[0020] In a preferred technical solution of the present invention, the liquid absorption multiple of the swollen residue of the ion cross-linked polymer after swelling in simulated intestinal fluid for 1 hour is no higher than 80% of the liquid absorption multiple of the ion cross-linked polymer after swelling in 1 / 10 diluted simulated gastric fluid at pH=2.5 for 1 hour.

[0021] The present invention also provides a method for preparing the ionomer, which comprises at least the following steps:

[0022] S1. Mix the raw materials with water in the desired proportion until they are completely dispersed to obtain a water mixture;

[0023] S2. Drying the aqueous mixture at a temperature of 50-105°C to obtain the ion cross-linked polymer.

[0024] The second aspect of the present invention provides a food-grade super-absorbent calcium supplement particle, which contains an ion cross-linked polymer, the ion cross-linked polymer at least contains a composite cross-linking agent and a water-soluble polymer with a carboxyl group or its sodium salt on the side group, the composite cross-linking agent is a composite of a calcium salt and an anionic cross-linking agent with a carboxyl group or its sodium salt on the side group. The ion cross-linked polymer is cross-linked by the physical action between calcium ions and carboxyl groups, and no chemical reaction occurs between the raw materials.

[0025] The calcium salt is selected from calcium citrate, a combination of calcium citrate and calcium malate, a combination of calcium citrate and a water-soluble calcium salt, a combination of a water-soluble citrate and a water-soluble calcium salt, wherein the water-soluble citrate is selected from sodium citrate, potassium citrate and a combination thereof, and the water-soluble calcium salt is selected from calcium lactate, calcium gluconate, calcium ascorbate and a combination thereof.

[0026] The anionic crosslinking agent is selected from sodium alginate. The water-soluble polymer having a carboxyl group or its sodium salt on the side group is selected from sodium carboxymethyl cellulose, and the viscosity of a 1% aqueous solution prepared from the sodium carboxymethyl cellulose at 25° C. is 50-4000 mPa·s; the sodium carboxymethyl cellulose is type 6 or type 9.

[0027] The mass ratio of sodium carboxymethyl cellulose to sodium alginate is 3:2-9:1, the mass ratio of sodium alginate to calcium ions is 20:1-10:1; and the molar ratio of citrate to calcium ions is 3:10-7:10.

[0028] The food-grade super-absorbent calcium supplement particles may or may not contain other food additives, and the food-grade super-absorbent calcium supplement particles only contain physical crosslinks and do not contain crosslinking agents that form chemical crosslinks with any raw materials.

[0029] The food-grade super-absorbent calcium supplement particles have a liquid absorption multiple of not less than 50 times after swelling for 1-4 hours in a 1 / 10 diluted simulated gastric juice at pH = 2.5, and the liquid absorption multiple after swelling for 4 hours varies by no more than ±25% compared with the liquid absorption multiple after swelling for 1 hour; the liquid absorption multiple of the swollen residue after swelling for 1 hour in simulated small intestinal fluid is not higher than 80% of the liquid absorption multiple after swelling for 1 hour in a 1 / 10 diluted simulated gastric juice at pH = 2.5.

[0030] In the preferred technical solution of the present invention, the particle size of the food-grade super-absorbent calcium supplement particles is 0.1-1 mm.

[0031] In a preferred technical solution of the present invention, the liquid absorption multiple of the food-grade super-absorbent calcium supplement particles after swelling for 4 hours in a 1 / 10 diluted simulated gastric fluid at pH = 2.5 varies by no more than ±10% compared with the liquid absorption multiple after swelling for 1 hour.

[0032] In the preferred technical solution of the present invention, the liquid absorption multiple of the swollen residue of the food-grade superabsorbent calcium supplement particles after swelling in simulated intestinal fluid for 1 hour is no higher than 70% of the liquid absorption multiple of the swollen residue after swelling in 1 / 10 diluted simulated gastric fluid at pH = 2.5 for 1 hour.

[0033] The present invention also provides a method for preparing the food-grade super-absorbent calcium supplement granules, which comprises at least the following steps:

[0034] S1. Mixing the raw materials with water until they are completely dispersed and uniformly dispersed to obtain a water mixture; wherein the sum of the mass of sodium carboxymethyl cellulose and sodium alginate is not more than 5% of the total mass;

[0035] S2. Transfer the water mixture to a non-stick container;

[0036] S3. Drying the aqueous mixture at a temperature of 50-105 ° C to obtain a solid composite;

[0037] S4. The obtained solid composite is crushed and sieved to obtain the food-grade super-absorbent calcium supplement particles;

[0038] The water is drinking purified water or drinking deionized water.

[0039] In a preferred technical solution of the present invention, the method for preparing the food-grade super-absorbent calcium supplement particles further comprises the following premixing step S0 before the step S1:

[0040] S0. Mix sodium carboxymethyl cellulose, sodium alginate and drinking water to obtain micelles; wherein the sum of the mass of sodium carboxymethyl cellulose and sodium alginate accounts for 15-20% of the total mass of the micelles.

[0041] In a preferred technical solution of the present invention, in the anti-sticking container, the water mixture is spread as a coating not exceeding 5 cm thick.

[0042] In a preferred technical solution of the present invention, the drying temperature in the step S3 of the method for preparing the food-grade super-absorbent calcium supplement particles is 70-80°C.

[0043] The third aspect of the present invention provides a product that provides a sense of satiety, wherein the product that provides a sense of satiety contains 0.1-99.9% by mass of the food-grade super-absorbent calcium supplement particles as described above. The product that provides a sense of satiety is a food, a medicine or a medical device. The food is in the form of a solid beverage, candy, or pet food; the medicine or medical device is in the form of a tablet, capsule, or granule.

[0044] Compared with the prior art, the present invention has the following beneficial effects:

[0045] 1. The ion cross-linked polymers provided by the present invention have a liquid absorption multiple of not less than 40 times in an acidic solution of pH=2.5. Based on the ion cross-linked polymers obtained by some preferred technical solutions, the food-grade superabsorbent calcium supplement particles provided by the present invention swell at a high multiple in the stomach but dissociate in the intestine. The liquid absorption multiple of the obtained particles after swelling in a 1 / 10 diluted simulated gastric fluid at pH=2.5 for 1-4 hours is not less than 50 times, and some proportion products are not less than 80 times, and some proportion products have stable swelling performance in the gastric environment pH, and the liquid absorption multiple after swelling in a 1 / 10 diluted simulated gastric fluid at pH=2.5 for 4 hours varies by no more than ±10% compared with the liquid absorption multiple after swelling for 1 hour. At the same time, the liquid absorption multiple of the swelling residue of the obtained particles after swelling in simulated small intestinal fluid for 1 hour is not higher than 80% of the liquid absorption multiple after swelling in simulated gastric fluid for 1 hour, and some proportion products dissociate faster and have less residue. The product containing the food-grade super-absorbent calcium supplement granules of the present invention can not only provide a strong sense of fullness, but also greatly reduce the probability of occurrence of side effects such as intestinal obstruction.

[0046] 2. The calcium salt in the ion cross-linked polymer of the present invention preferably uses a slightly soluble calcium salt, more preferably a slightly soluble organic calcium salt. Unlike using only soluble calcium salts (such as calcium chloride, calcium lactate, etc.), its lower dissociation constant and the steric hindrance effect brought by the organic acid group make the resulting anionic cross-linking agent have good dispersibility in water, and further enhance its dissolution equilibrium and cross-linking stability in acidic solution. For example, a mixed solution of sodium alginate and calcium citrate can be filtered using a sand core funnel of model G1 (aperture 20-30 microns) without obvious precipitation, which provides conditions for realizing uniform blending with other raw materials in water. On the other hand, a slightly soluble organic calcium salt can be realized by a combination of a water-soluble citrate and a water-soluble calcium salt. After dissolving the two in water, a clear and transparent solution can be obtained in a short time, which is convenient for quickly realizing uniform blending.

[0047] 3. The calcium salt involved in the food-grade super-absorbent calcium supplement granules of the present invention, especially the calcium citrate in the preferred technical solution, is an ideal calcium supplement. When the granules are dissociated in the intestine, the calcium ions released are not only harmless to the human body, but can also be absorbed and utilized by the human body, and can provide a composite effect of supplementing absorbable calcium without using additional additives. Moreover, the composition of the ion cross-linked polymer is insensitive to the content of calcium citrate within a certain range, which is conducive to increasing or decreasing the content of calcium ions according to the calcium supplementation needs while keeping the liquid absorption multiple relatively stable.

[0048] 4. All raw materials used to prepare the food-grade super-absorbent calcium supplement granules are food-grade, such as sodium carboxymethyl cellulose, sodium alginate, sodium citrate, potassium citrate, etc., which are all in GB 2760-2014 "National Food Safety Standard for the Use of Food Additives" "Table A.2 List of Food Additives that Can Be Used in Various Foods in Proper Amounts According to Production Needs". The various ingredients in the food-grade super-absorbent calcium supplement granules are widely used as food additives, and in some formulas, there are only physical interactions between the ingredients. No chemical reaction occurs during the processing, and no new chemical substances are produced. The actual ingredients of the product are controllable, and compared with products with chemical cross-linking, they are safer for the human body.

[0049] 5. In the preparation process of the food-grade super-absorbent calcium supplement particles, there is no need to use dangerous goods such as flammable solvents, strong acids, and strong bases. There is no need for high pressure or reduced pressure during mixing. After one-time drying, high-temperature induced cross-linking such as esterification and other similar secondary drying processes are not required, and there is no need to perform complex operations such as dripping, centrifugation, washing, freeze-thawing, and freeze-drying. Furthermore, when using high-viscosity raw materials, the mixing time of the solution can be greatly reduced by premixing at a high concentration, and the mixing can be carried out efficiently at room temperature, which can reduce the total mixing time from dozens of hours or more than ten hours to a few hours. It is more suitable for large-scale industrial production and has a very high commercial prospect.

[0050] These and other features and advantages of the present invention will become apparent with reference to the following description of the embodiments, examples and appended claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 The state of the particles obtained in Example A1 after swelling in a 1 / 10 diluted simulated gastric fluid without enzyme at pH = 2.5 for 4 hours (left) is compared with the state of the particles in the solution after swelling in a simulated small intestinal fluid without enzyme at pH = 6.8 for 1 hour (right)

[0052] Figure 2The particles obtained in Example A1 were swollen in a 1 / 10 diluted simulated gastric fluid without enzyme at pH = 2.5 for 4 hours, filtered through a sand core funnel and then transferred to the residue on the filter paper (left) and the particles were swollen in a simulated small intestinal fluid without enzyme at pH = 6.8 for 1 hour, filtered through a sand core funnel and then transferred to the residue on the filter paper (right)

[0053] Figure 3 Comparison of calcium citrate and water mixture (left), calcium citrate, sodium alginate and water mixture (middle), calcium citrate, sodium alginate and sodium carboxymethyl cellulose water mixture (right)

[0054] Figure 4 Comparison of the residues of a mixture of calcium citrate, sodium alginate, and water (lower left) and a mixture of calcium chloride, sodium alginate, and water (upper right) after filtration through a G1 sand core funnel DETAILED DESCRIPTION

[0055] Ionomer

[0056] The invention provides an ion cross-linked polymer, which at least contains a composite cross-linking agent and a water-soluble polymer containing a carboxyl group or its sodium salt at the side group. The composite cross-linking agent is formed by compounding a calcium salt and an anionic cross-linking agent containing a carboxyl group or its sodium salt at the side group. The ion cross-linked polymer is cross-linked by the physical action between calcium ions and carboxyl groups, and no chemical reaction occurs between the raw materials.

[0057] Wherein, the calcium salt is preferably a slightly soluble calcium salt or a calcium salt composition containing it. The slightly soluble calcium salt is selected from calcium citrate, calcium malate, and calcium sulfate, and the composition containing slightly soluble calcium salt is selected from the composition of calcium citrate and other calcium salts, the composition of calcium malate and other calcium salts, the composition of calcium sulfate and other calcium salts, the composition of water-soluble citrate and water-soluble calcium salt, the composition of water-soluble malate and water-soluble calcium salt, the composition of water-soluble sulfate and water-soluble calcium salt. Since the steric hindrance brought by sulfate in calcium sulfate is less than that of organic acid radical, and the scope of use and dosage as a food additive in the food field are limited, the calcium salt is further preferably selected from slightly soluble organic calcium salt and a combination containing it, specifically, slightly soluble organic calcium salt and a combination containing it are selected from calcium citrate, calcium malate, the composition of calcium citrate and other calcium salts, the composition of calcium malate and other calcium salts, the composition of water-soluble citrate and water-soluble calcium salt, the composition of water-soluble malate and water-soluble calcium salt. The water-soluble citrate is selected from sodium citrate, potassium citrate and a combination thereof, and the water-soluble calcium salt is preferably selected from water-soluble organic calcium salts, more preferably from calcium lactate, calcium gluconate, calcium ascorbate and a combination thereof.

[0058] In a preferred embodiment of the present invention, the calcium salt is selected from calcium citrate. Since the use of calcium citrate alone is simpler to operate than using a compounded composition, it is more preferred.

[0059] In another preferred embodiment of the present invention, the calcium salt is selected from a combination of calcium citrate and calcium malate. Since calcium citrate and calcium malate are often used in the food industry to make the product have a better flavor, this is also preferred.

[0060] In another preferred embodiment of the present invention, the calcium salt is selected from a combination of calcium citrate and a water-soluble calcium salt, preferably a combination of calcium citrate and calcium lactate. First, the combination of calcium citrate and other calcium salts can flexibly adjust the ratio of citrate and calcium ions as needed, which cannot be achieved by using only calcium citrate; second, calcium lactate not only has good solubility but also good thermal stability, and the range and amount allowed to be added as a food additive are also very wide. Therefore, calcium citrate and a water-soluble calcium salt are also preferred, especially a combination of calcium citrate and calcium lactate is more preferred.

[0061] In another preferred embodiment of the present invention, the calcium salt is selected from a water-soluble citrate and a water-soluble calcium salt composition, preferably a composition of sodium citrate and a water-soluble calcium salt, a composition of potassium citrate and a water-soluble calcium salt, further preferably a composition of sodium citrate and calcium lactate, a composition of potassium citrate and calcium lactate, and most preferably a combination of potassium citrate and calcium lactate. First, the use of a combination of soluble citrate and other calcium salts can flexibly adjust the ratio of citrate and calcium ions as needed, which cannot be achieved by using only calcium citrate; second, potassium citrate and calcium lactate will not form a large amount of insoluble precipitates in a short time after mixing at a low concentration, which is conducive to processing; third, calcium lactate not only has good solubility but also good thermal stability, and the range and amount allowed to be added as a food additive are also very wide; fourth, excessive sodium ion intake can cause harm to the human body, and the use of potassium citric acid instead of the commonly used sodium salt and other calcium salts can be well avoided.

[0062] Wherein, the anionic crosslinking agent having a carboxyl group or its sodium salt in the side group is selected from sodium alginate, linseed gum, low-ester pectin and a combination thereof. The anionic crosslinking agent is preferably selected from sodium alginate, linseed gum and a combination thereof, and is further preferably sodium alginate. Wherein, the viscosity of a 1% aqueous solution prepared from the sodium alginate at 20° C. is not particularly limited.

[0063] Wherein, the water-soluble polymer containing carboxyl or its sodium salt on the side group contains at least 0.5 carboxyl groups on average per repeating unit, and is selected from acrylic acid homopolymer and copolymer thereof, sodium acrylate homopolymer and copolymer thereof, polysaccharide polymer containing carboxyl or its sodium salt on the side group, and combinations thereof. The water-soluble polymer containing carboxyl or its sodium salt on the side group is preferably selected from sodium carboxymethyl cellulose, and the viscosity of the 1% aqueous solution prepared from the sodium carboxymethyl cellulose at 25°C is not less than 50mPa·s, preferably 50-4000mPa·s, more preferably 400-4000mPa·s, and most preferably 700-4000mPa·s; the degree of substitution of the sodium carboxymethyl cellulose is not less than 0.5, preferably 0.7-1.2.

[0064] In a preferred embodiment of the present invention, the anionic crosslinking agent is selected from sodium alginate, and the water-soluble polymer is selected from sodium carboxymethyl cellulose. The mass ratio of sodium carboxymethyl cellulose to sodium alginate is 1:1-9:1, preferably 3:2-9:1. The mass ratio of sodium alginate to calcium ions is 60:1-5:2, preferably 40:1-5:2, and more preferably 20:1-10:1. The molar ratio of the total number of negative charges of the acid radical ions of the sparingly soluble organic calcium salt to the total number of positive charges of the calcium ions is preferably 9:20-21:20. For example, when the sparingly soluble organic calcium salt is calcium citrate, the citrate radical is trivalent and the calcium ion is divalent, that is, the molar ratio of the citrate radical to the calcium ion is preferably 3:10-7:10.

[0065] The preparation method of the ion cross-linked polymer comprises at least the following steps:

[0066] S1. Mix the raw materials with water in the desired proportion until they are completely dispersed to obtain a water mixture;

[0067] S2. Drying the aqueous mixture at a temperature of 50-105°C to obtain the ion cross-linked polymer.

[0068] The ion cross-linked polymer has a liquid absorption multiple of not less than 40 times after swelling in a 1 / 10 diluted simulated gastric fluid at pH = 2.5 for 1-4 hours, preferably not less than 50 times, more preferably not less than 60 times, more preferably not less than 70 times, more preferably not less than 80 times, more preferably not less than 90 times, and more preferably not less than 100 times. The liquid absorption multiple of the ion cross-linked polymer after swelling in a 1 / 10 diluted simulated gastric fluid at pH = 2.5 for 4 hours preferably does not exceed ±25% compared with the liquid absorption multiple after swelling for 1 hour, more preferably does not exceed ±20%, more preferably does not exceed ±15%, preferably does not exceed ±10%, and most preferably does not exceed ±5%.

[0069] Among them, the 1 / 10 diluted simulated gastric juice with a pH of 2.5 is obtained by diluting the artificial gastric juice (pH = 1.5) of the 2020 edition of the Chinese Pharmacopoeia 10 times and then adjusting the pH to 2.5.

[0070] In a preferred embodiment of the present invention, the liquid absorption multiple of the swollen residue after swelling in simulated small intestinal fluid for 1 hour of the ion cross-linked polymer is not higher than 80% of the liquid absorption multiple after swelling in 1 / 10 simulated gastric fluid for 1 hour, more preferably not higher than 70% of the liquid absorption multiple after swelling in 1 / 10 simulated gastric fluid for 1 hour, and most preferably not higher than 60% of the liquid absorption multiple after swelling in 1 / 10 simulated gastric fluid for 1 hour.

[0071] Among them, the simulated small intestinal fluid is the artificial small intestinal fluid of the 2020 edition of the Chinese Pharmacopoeia, with a pH value of 6.8.

[0072] Food grade super absorbable calcium supplement granules

[0073] The present invention also provides a food-grade super-absorbent calcium supplement particle, characterized in that the food-grade super-absorbent calcium supplement particle contains an ion cross-linked polymer, the ion cross-linked polymer contains at least a composite cross-linking agent and a water-soluble polymer with a carboxyl group or its sodium salt on the side group, the composite cross-linking agent is a composite of a calcium salt and an anionic cross-linking agent with a carboxyl group or its sodium salt on the side group. The ion cross-linked polymer is cross-linked by the physical action between calcium ions and carboxyl groups, and no chemical reaction occurs between the raw materials.

[0074] Wherein, the calcium salt is selected from calcium citrate, a calcium citrate and calcium malate composition, a calcium citrate and a water-soluble calcium salt composition, a water-soluble citrate and a water-soluble calcium salt composition, wherein the water-soluble citrate is selected from sodium citrate, potassium citrate and a combination thereof, and the water-soluble calcium salt is selected from calcium lactate, calcium gluconate, calcium ascorbate and a combination thereof. The calcium salt is further preferably selected from calcium citrate, a calcium citrate and calcium malate composition, a calcium citrate and calcium lactate composition, a sodium citrate and calcium lactate composition, a potassium citrate and calcium lactate composition, and is most preferably selected from calcium citrate, a calcium citrate and calcium malate composition, a calcium citrate and calcium lactate composition, a potassium citrate and calcium lactate composition.

[0075] Wherein, the anionic crosslinking agent is selected from sodium alginate, and the viscosity of the 1% aqueous solution prepared from the sodium alginate at 20°C is not particularly limited, and is preferably 20-1200 mPa·s; the water-soluble polymer containing a carboxyl group or its sodium salt on the side group is selected from sodium carboxymethyl cellulose, and the viscosity of the 1% aqueous solution prepared from the sodium carboxymethyl cellulose at 25°C is 50-4000 mPa·s, preferably 400-4000 mPa·s, and more preferably 700-4000 mPa·s. The sodium carboxymethyl cellulose is type 6 or type 9. Since the carboxyl content in type 9 sodium carboxymethyl cellulose is higher, it is conducive to obtaining particles with a higher liquid absorption multiple, so the sodium carboxymethyl cellulose is preferably type 9.

[0076] The mass ratio of sodium carboxymethyl cellulose to sodium alginate is 1:1-9:1, preferably 3:2-9:1. The mass ratio of sodium alginate to calcium ions is 60:1-5:2, preferably 40:1-5:2, and more preferably 20:1-10:1.

[0077] In a preferred embodiment of the present invention, the molar ratio of citrate to calcium ion is 3:10-7:10.

[0078] The method for preparing the food-grade super-absorbent calcium supplement granules comprises at least the following steps:

[0079] S1. Mixing the raw materials with water until they are completely dispersed and uniformly dispersed to obtain a water mixture; wherein the sum of the mass of sodium carboxymethyl cellulose and sodium alginate is not more than 5% of the total mass;

[0080] S2. Transfer the water mixture to a non-stick container;

[0081] S3. Drying the aqueous mixture at a temperature of 50-105 ° C to obtain a solid composite;

[0082] S4. The obtained solid composite is crushed and sieved to obtain the food-grade super-absorbent calcium supplement particles.

[0083] As a preferred embodiment of the preparation method of the present invention, the following premixing step S0 is also included before the step S1:

[0084] S0. Mix sodium carboxymethyl cellulose, sodium alginate and drinking water to obtain micelles; wherein the sum of the mass of sodium carboxymethyl cellulose and sodium alginate accounts for 15-20% of the total mass.

[0085] In a preferred embodiment of the present invention, the calcium salt in the food-grade super-absorbent calcium supplement granules is selected from calcium citrate, a combination of calcium citrate and calcium malate, and a combination of calcium citrate and calcium lactate. The preparation method of the food-grade super-absorbent calcium supplement granules comprises at least the following steps:

[0086] S0. Mixing sodium carboxymethyl cellulose, sodium alginate and drinking water to obtain micelles; wherein the mass of the solute accounts for 15-20% of the total mass;

[0087] S1. sequentially adding the micelle obtained in S0, water, and calcium salt, and mixing until completely dispersed to obtain a water mixture; wherein the sum of the mass of sodium carboxymethyl cellulose and sodium alginate is not more than 5% of the total mass;

[0088] S2. Transfer the water mixture to a non-stick container;

[0089] S3. Drying the aqueous mixture at a temperature of 50-105 ° C to obtain a solid composite;

[0090] S4. The obtained solid composite is crushed and sieved to obtain the food-grade super-absorbent calcium supplement particles.

[0091] In another preferred embodiment of the present invention, the calcium salt in the food-grade super-absorbent calcium supplement granules is selected from a combination of sodium citrate and calcium lactate or a combination of potassium citrate and calcium lactate, and the preparation method of the food-grade super-absorbent calcium supplement granules comprises at least the following steps:

[0092] S0. Mixing sodium carboxymethyl cellulose, sodium alginate and drinking water to obtain micelles; wherein the mass of the solute accounts for 15-20% of the total mass;

[0093] S1. Mix sodium citrate or potassium citrate, calcium lactate and water until dissolved, add the micelle obtained in S0, and mix until completely dispersed to obtain a water mixture; wherein the sum of the mass of sodium carboxymethyl cellulose and sodium alginate is not more than 5% of the total mass;

[0094] S2. Transfer the water mixture to a non-stick container;

[0095] S3. Drying the aqueous mixture at a temperature of 50-105 ° C to obtain a solid composite;

[0096] S4. The obtained solid composite is crushed and sieved to obtain the food-grade super-absorbent calcium supplement particles.

[0097] The drinking water is purified water or deionized water.

[0098] In a preferred embodiment of the present invention, the sum of the mass of sodium carboxymethyl cellulose and sodium alginate in step S0 preferably accounts for 15-19% of the total mass, more preferably 15-18% of the total mass, and most preferably 15-17% of the total mass. When the water content of the micelle is higher, the sodium carboxymethyl cellulose and sodium alginate raw material powders in the micelle are more fully infiltrated by water, which is conducive to further shortening the mixing time of step S1.

[0099] The anti-stick container is preferably a container made of polytetrafluoroethylene or polypropylene, or a container of other materials covered with an anti-stick film. The anti-stick film is preferably a food contact anti-stick cloth, polytetrafluoroethylene film, or polypropylene film.

[0100] Wherein, in the anti-stick container, the water mixture is preferably spread as a coating no thicker than 5 cm, further preferably spread as a coating no thicker than 4 cm, further preferably spread as a coating no thicker than 3 cm, further preferably spread as a coating no thicker than 2 cm.

[0101] The drying method is not particularly limited, and is preferably air drying or vacuum drying.

[0102] The drying temperature is preferably 70-105°C. On the one hand, when the drying temperature is low, the drying time will be greatly prolonged and the production efficiency will be greatly reduced. On the other hand, a relatively mild drying temperature is conducive to the reproduction of harmful microorganisms in the water mixture. Considering that the lethal temperature of general bacteria is about 68°C, it is more preferred that the drying temperature is not less than 70°C.

[0103] Wherein, the drying temperature is further preferably 70-80°C. When the drying temperature is 85-90°C, for a water mixture with a higher concentration and a thicker coating, a dry and dense epidermis is easily formed on the surface of the water mixture first, and the evaporation of the internal water is prevented, which requires a longer drying time. Using a higher drying temperature not only does not improve the drying efficiency, but wastes energy. Therefore, it is more preferred that the drying temperature is not higher than 80°C.

[0104] Wherein, the particle size of the particles is preferably 0.1-1mm, and more preferably 0.4-1mm. When the powder with a particle size of less than 0.1mm meets water, it quickly agglomerates into a large block of gel and is difficult to disperse. When the particle size is 0.1-0.4mm, a small amount of dispersant is added and mixed with water to maintain the granular feel, so the particle size of the particles is preferably 0.1-1mm. When the particle size is 0.4-1mm, even if no dispersant is added, mixing with water can still maintain the granular feel. Therefore, the particle size of the particles is more preferably 0.4-1mm.

[0105] The liquid absorption multiple of the food-grade super-absorbent calcium supplement particles after swelling in 1 / 10 simulated gastric fluid for 1-4 hours is not less than 60 times, preferably not less than 70 times, more preferably not less than 80 times, more preferably not less than 90 times, and more preferably not less than 100 times. The liquid absorption multiple of the food-grade super-absorbent calcium supplement particles after swelling in 1 / 10 simulated gastric fluid with pH=2.5 for 4 hours is preferably not more than ±25% compared with the liquid absorption multiple after swelling for 1 hour, more preferably not more than ±20%, more preferably not more than ±15%, more preferably not more than ±10%, and most preferably not more than ±5%. Through its stable liquid absorption performance, it occupies a certain volume in the stomach and provides a sense of fullness for a longer period of time after eating.

[0106] The liquid absorption multiples of the swollen residue of the food-grade super-absorbent calcium supplement particles after swelling in simulated small intestinal fluid for 1 hour are not higher than 80% of the liquid absorption multiples after swelling in 1 / 10 simulated gastric fluid for 1 hour, preferably not higher than 70% of the liquid absorption multiples after swelling in 1 / 10 simulated gastric fluid for 1 hour, and more preferably not higher than 60% of the liquid absorption multiples after swelling in 1 / 10 simulated gastric fluid for 1 hour.

[0107] The food-grade super-absorbable calcium supplement particles may or may not contain other food additives. For example, the other food additives include but are not limited to sugar alcohols, oligofructose, L-carnitine, probiotics, animal extracts, plant extracts, mushroom extracts, etc., but do not contain cross-linking agents that form chemical cross-links with any raw materials.

[0108] Products that provide a high degree of satiety

[0109] The present invention also provides a product that provides a high-efficiency satiety feeling, wherein the product contains 0.1-99.9% by mass of the aforementioned food-grade super-absorption calcium supplement particles.

[0110] In a preferred embodiment of the present invention, the product is food, medicine or medical device, wherein the food is in the form of solid beverage, candy or pet food; the medicine or medical device is in the form of tablet, capsule or granule.

[0111] One embodiment of the present invention provides a solid beverage. For example, the solid beverage comprises at least the following components:

[0112] Food grade super absorbable calcium supplement granules, 100 parts by weight;

[0113] Citric acid, 0.01-5 parts by weight;

[0114] Sweetener, 0.01-5 parts by weight;

[0115] Natural fruit powder, 10-100 parts by mass.

[0116] The solid beverage may also include but is not limited to other food raw materials or food additives such as hydrolyzed collagen, white kidney bean extract, sugar alcohol, oligofructose, L-carnitine, probiotics, other animal extracts, other plant extracts, mushroom extracts, etc.

[0117] The above components are mixed according to the formula ratio and packed into bags to obtain a solid beverage providing efficient satiety of the present invention. 20-40 minutes before lunch or dinner, pour the solid beverage into 200 mL of room temperature water, stir quickly until the particles are basically dispersed, drink it within three minutes, and then drink 200 mL of water; eat normally or in reduced amounts after 30 minutes, which can effectively delay the occurrence of hunger.

[0118] One embodiment of the present invention provides a compressed candy. For example, the compressed candy comprises at least the following components:

[0119] Food grade super absorbable calcium supplement granules, 100 parts by weight;

[0120] Mannitol, 10-30 parts by weight;

[0121] Isomalt, 10-30 parts by weight;

[0122] Magnesium stearate, 1-2 parts by mass;

[0123] Citric acid, 0.1-5 parts by mass;

[0124] Other sweeteners: 0.1-5 parts by weight.

[0125] After the particles and auxiliary materials are fully mixed, they are tableted using a tablet press, packaged and sealed to obtain the candy providing a high-efficiency satiety feeling of the present invention.

[0126] Take the compressed candy with 400 mL of water 20-40 minutes before lunch or dinner; eat normally or in reduced amounts 30 minutes later, which can effectively delay the occurrence of hunger.

[0127] One embodiment of the present invention provides a soft candy. As an example, the soft candy comprises at least the following components:

[0128] Food grade super absorbable calcium supplement granules, 100 parts by weight;

[0129] Gelatin, 10-30 parts by weight;

[0130] Water, 50-200 parts by mass;

[0131] Sugar alcohol, 100-500 parts by weight;

[0132] Acidulant, 3-8 parts by weight;

[0133] Concentrated juice, 50-150 parts by weight.

[0134] The raw materials except the food-grade super-absorbent calcium supplement particles are mixed uniformly at 90° C., and then the particles and the mixed liquid are fully mixed and poured into a mold for cooling and forming. After being ejected from the mold, an anti-sticking agent is applied, and the package is sealed to obtain a soft candy providing efficient satiety of the present invention.

[0135] 20-40 minutes before lunch or dinner, eat the soft candy and drink 300-500 mL of water; 30 minutes later, eat normally or in reduced amounts, which can effectively delay the occurrence of hunger.

[0136] One embodiment of the present invention provides a capsule. As an example, the capsule comprises at least the following components:

[0137] Food grade super absorbable calcium supplement granules, 100 parts by weight;

[0138] Disintegrant 5-150 parts by weight.

[0139] Take the capsule with 400 mL of water 20-40 minutes before lunch or dinner; eat a normal or reduced meal 30 minutes later to effectively delay the occurrence of hunger.

[0140] The above examples of components of solid beverages, compressed candies, soft candies, and capsules are only for further illustrating the present invention in detail, and do not limit the protection scope of the present invention.

[0141] In one embodiment of the present invention, each single serving of the product providing a high sense of satiety contains no more than 3 g of food-grade superabsorbent calcium supplement particles, preferably 0.5-3 g, more preferably 1-3 g, more preferably 1.5-3 g, and most preferably 2-3 g.

[0142] Liquid absorption multiple measurement and calculation method

[0143] In the present invention, the measurement and calculation of the liquid absorption multiples in different simulated liquids are carried out as follows:

[0144] - Accurately weigh 0.0200±0.0005g of particles with a particle size of 0.4-1mm, and record the exact value as M0;

[0145] -Put the weighed particles into a 50mL beaker that has been preheated in a 37°C water bath and contains 20mL of simulated liquid (i.e., the mass ratio of particles to simulated liquid is 1:1000), and start timing;

[0146] - Use a 60mL G1 sand core funnel to negatively filter 20mL of deionized water, carefully wipe the residual liquid at the mouth of the funnel (the slender tube at the lower end) with a filter paper strip, accurately weigh the mass of the sand core funnel to 0.1mg, and record the accurate value as M1;

[0147] - After continuous magnetic dispersion and swelling for a specific period of time in a 37°C water bath, filter the simulated liquid through the above 60mL G1 sand core funnel under negative pressure, carefully wipe the residual liquid at the mouth of the funnel with a filter paper strip, and accurately weigh the mass of the sand core funnel containing the filtered residue to 0.1 mg, and record the accurate value as M2;

[0148] - Calculate the liquid absorption multiple of the particles according to the following formula: Liquid absorption multiple = (M2-M1) / M0-1.

[0149] Raw material viscosity measurement method

[0150] The viscosity data provided by the raw material supplier was used and measured using a numerical rotational viscometer to confirm whether the measured value was within the claimed range.

[0151] Among them, the viscosity of sodium carboxymethyl cellulose is carried out according to A.4 of the national standard "GB1886.232-2016 National Food Safety Standard Food Additive Sodium Carboxymethyl Cellulose".

[0152] Among them, the viscosity of sodium alginate is carried out according to A.3 of the national standard "GB1886.243-2016 National Food Safety Standard Food Additive Sodium Alginate".

[0153] The present invention is further described below in conjunction with some specific embodiments. The specific embodiments are to further illustrate the present invention in detail, but not to limit the scope of protection of the present invention. Unless otherwise specified, the raw materials used in the embodiments are all commercially available food-grade raw materials that meet the corresponding national standards.

[0154] Group 1: Using different anionic crosslinkers

[0155] Embodiment A1, 2

[0156] 80 parts by mass of sodium carboxymethyl cellulose (viscosity 3000-4000 mPa·s), 20 parts by mass of sodium alginate (viscosity 750-850 mPa·s) or linseed gum, and 1 part by mass of calcium citrate tetrahydrate containing calcium ions are dispersed in 4900 parts by mass of deionized water until uniform and transparent; the mixed solution is transferred to a PP food contact plastic container and air-dried at 70° C. for 24 hours; and 0.4-1 mm component particles are crushed and sieved for subsequent swelling performance testing.

[0157] Example A3

[0158] 90 parts by mass of sodium carboxymethyl cellulose (viscosity 3000-4000 mPa·s), 10 parts by mass of low-ester pectin, and calcium citrate tetrahydrate containing 0.5 parts by mass of calcium ions were dispersed in 4900 parts by mass of deionized water until uniform and transparent; the mixed solution was transferred to a PP food contact plastic container and dried at 70°C for 24 hours; and 0.4-1 mm component particles were crushed and sieved for subsequent swelling performance testing.

[0159] Table 1 lists the liquid absorption multiples of the particles obtained in Example A1-3 in 1 / 10 diluted simulated gastric fluid (pH=2.5) and simulated small intestinal fluid (pH=6.8):

[0160] Table 1

[0161] Example No. Anionic crosslinking agent pH=2.51h pH=2.54h pH=6.81h Example A1 Sodium alginate 132.8 132.6(-0.2%) 47.5(-64.2%) Example A2 Flaxseed Gum 111.0 88.5(-20.3%) 54.8(-50.6%) Example A3 Low ester pectin 109.2 114.4(+4.8%) 107.1(-1.8%)

[0162] Note: The percentage in brackets is the change of the absorption multiple relative to the absorption multiple obtained when pH = 2.51h, the same below.

[0163] Examples A1-A3 show that various anionic crosslinking agents can be compounded with calcium salts and form ion crosslinked polymers with sodium carboxymethyl cellulose. Among them, the ion polymer obtained using low-ester pectin has good and stable swelling performance in 1 / 10 diluted simulated gastric juice at pH = 2.5 and in simulated small intestinal juice at pH = 6.8. The ion polymer obtained using sodium alginate and flaxseed gum has good degradability in simulated small intestinal juice at pH = 6.8, and its liquid absorption multiple after swelling for 1 hour is about 50-65% lower than that in 1 / 10 diluted simulated gastric juice at pH = 2.5 after swelling for 1 hour, and the risk of consumption is low. Therefore, sodium alginate and flaxseed gum are preferably used for the preparation of food-grade superabsorbent calcium supplement particles and applied to different types of products. Furthermore, the ionic polymer obtained using sodium alginate is more stable in 1 / 10 diluted simulated gastric juice at pH = 2.5, that is, the liquid absorption multiple changes within ±10% when swelling for 4 hours compared with swelling for 1 hour, while the liquid absorption multiple of the ionic polymer obtained using flaxseed gum decreases with the extension of swelling time in diluted simulated gastric juice. Therefore, the ionic polymer obtained using sodium alginate is more suitable for the preparation of food-grade super-absorbent calcium supplement particles and can be used in different types of products that provide a strong sense of fullness.

[0164] In addition, the state of the particles obtained in Example A1 using sodium alginate after swelling in a 1 / 10 diluted simulated gastric fluid without enzyme at pH = 2.5 for 4 hours and in a simulated small intestinal fluid without enzyme at pH = 6.8 for 1 hour ( Figure 1 , Note: Enzyme-free solution is used here for the convenience of recording and observation). After swelling in a pH = 2.5 solution for 4 hours, there are still a large number of translucent white particles visible to the naked eye in the solution, while after swelling in a pH = 6.8 solution for 1 hour, there are only a few translucent white particles visible to the naked eye. After filtration, transfer the residue in the funnel to the filter paper ( Figure 2), there are a lot of gel particles in the filtrate of pH=2.5 solution, while there are fewer gel particles in the filtrate of pH=6.8 solution, and they are all amorphous soft gels. A considerable part of them is absorbed into the sand core plate of the funnel, and it is difficult to completely collect and transfer them from the funnel, indicating that they have been mostly dissociated under pH=6.8 conditions, which is manifested by a significant reduction in the liquid absorption multiple.

[0165] Group 2: Using different molar ratios of citrate to calcium

[0166] Examples B1-B7

[0167] 80 parts by mass of sodium carboxymethyl cellulose (viscosity 3000-4000 mPa·s), 20 parts by mass of sodium alginate (viscosity 750-850 mPa·s), 1 part by mass of calcium lactate containing calcium ions, and a certain amount of potassium citrate are dispersed in 4900 parts by mass of deionized water until uniform and transparent; the mixed solution is dried in a PP plastic container at 70° C. until the moisture content is less than 10%; and 0.4-1 mm component particles are crushed and sieved for subsequent swelling performance testing.

[0168] Table 2 lists the liquid absorption multiples of the particles obtained in Examples A1-A3 in 1 / 10 diluted simulated gastric fluid (pH=2.5) and simulated small intestinal fluid (pH=6.8):

[0169] Table 2

[0170] Example No. Citrate:Calcium ion molar ratio pH=2.51h pH=2.54h pH=6.81h Example B1 4:15 130.7 92.3(-29.4%) 41.1(-68.6%) Example B2 3:10 117.8 113.2(-3.9%) 44.8(-62.0%) Example B3 1:2 124.0 116.5(-6.0%) 56.2(-54.7%) Example B4 3:5 140.5 137.1(-2.4%) 53.8(-61.7%) Example B5 2:3 123.5 122.3(-1.0%) 43.1(-65.1%) Example B6 7:10 115.8 118.8(+2.6%) 45.6(-60.6%) Example B7 11:15 140.3 95.4(-32.0%) 40.3(-71.3%)

[0171] Examples B1-B7 show that when the molar ratio of citric acid:calcium ion in the citrate is 3:10-7:10, the obtained particles swell in a 1 / 10 dilute gastric release simulated solution with a pH of 2.5 for 1 hour and 4 hours with a liquid absorption multiple change of less than ±10%, which is more suitable for the preparation of food-grade super-absorbent calcium supplement particles and can be used in different types of products that provide a strong sense of fullness.

[0172] Group 3: Using different types of calcium salts and calcium salt combinations

[0173] Examples C1-C5

[0174] 80 parts by mass of sodium carboxymethyl cellulose (viscosity 3000-4000 mPa·s), 20 parts by mass of sodium alginate (viscosity 750-850 mPa·s), and a calcium salt or a calcium salt composition containing 1 part by mass of calcium ions are dispersed in 4900 parts by mass of deionized water until uniform and transparent; the mixed solution is transferred to a PP food contact plastic container and air-dried at 70° C. for 24 hours; and 0.4-1 mm component particles are crushed and sieved for subsequent swelling performance testing.

[0175] Table 3 lists the liquid absorption multiples of the particles obtained in Examples A1, B5, C1-C5 in 1 / 10 diluted simulated gastric fluid (pH=2.5) and simulated small intestinal fluid (pH=6.8):

[0176] Table 3

[0177]

[0178]

[0179] Embodiments A1, B5, C1-C5 show that various types of calcium salts or calcium salt compositions can be used to compound with sodium alginate and further form ion crosslinked polymers with sodium carboxymethyl cellulose. Among them, if calcium salts with higher solubility are used, such as embodiments C3 and C5, the liquid absorption multiples of the obtained particles swelling in 1 / 10 diluted simulated gastric juice at pH=2.5 for 1 hour and 4 hours vary by more than ±25%, which is unfavorable for controlling the swelling of the particles in the stomach. While using slightly soluble calcium salts or calcium salt compositions containing them, such as embodiments A1, B5, C1, C2, and C4, the liquid absorption multiples of the particles swelling in 1 / 10 diluted simulated gastric juice at pH=2.5 for 1 hour and 4 hours vary by less than ±25%, so it is more preferred. Furthermore, when a sparingly soluble organic calcium salt or a calcium salt composition containing the same is used, such as in Examples A1, B5, C1, and C2, the particles swell in a 1 / 10 diluted simulated gastric fluid at pH = 2.5 for 1 hour and 4 hours with a liquid absorption multiple change of less than ±10%, and therefore are more preferred.

[0180] In addition, according to the formula of Example A1, water, calcium citrate tetrahydrate, and sodium alginate were magnetically dispersed at 500 rpm for 4 hours to obtain a clear and transparent aqueous solution. Sodium carboxymethyl cellulose was added to the mixed solution, and the mixture was magnetically dispersed at 500 rpm for 6 hours to obtain a clear and transparent aqueous solution with a certain viscosity and fluidity ( Figure 3 , Figure 4 According to the formula of Example C5, water, calcium chloride, and sodium alginate were magnetically dispersed at 500 rpm for 4 hours to obtain a water mixture that was clear and transparent but contained a large number of millimeter-sized particles ( Figure 4 ). Sodium carboxymethyl cellulose was added to the mixture, and the magnetic dispersion was continued at 500 rpm for 6 hours, and a water mixture with a clear and transparent appearance but containing a large number of millimeter-sized particles was still obtained. By comparing the phenomena observed in the above Examples A1 and C5, it can be seen that the solubility of the calcium salt has an important influence on the morphology of the water mixture. Further, combined with the data in Table 3, it can be seen that the morphology of the water mixture will further affect the liquid absorption performance of the obtained particles.

[0181] Group 4: Using sodium carboxymethyl cellulose with different degrees of substitution and viscosities

[0182] Examples D1-D8

[0183] 80 parts by mass of sodium carboxymethyl cellulose, 20 parts by mass of sodium alginate (viscosity 750-850 mPa·s), and calcium citrate tetrahydrate containing 1 part by mass of calcium ions were dispersed in 4900 parts by mass of deionized water until uniform and transparent; the mixed solution was transferred to a PP food contact plastic container and dried at 70°C for 24 hours; and 0.4-1 mm component particles were crushed and sieved for subsequent swelling performance testing.

[0184] Table 4 lists the liquid absorption multiples of the particles obtained in Examples A1, D1-D8 in 1 / 10 diluted simulated gastric fluid (pH=2.5) and simulated small intestinal fluid (pH=6.8):

[0185] Table 4

[0186] Example No. Sodium Carboxymethyl Cellulose Parameters pH=2.51h pH=2.54h pH=6.81h Example D1 Type 9, 50-150 mPa·s 72.7 74.0(+1.8%) 9.0(-87.6%) Example D2 Type 6, 300-400 mPa·s 57.9 54.9(-5.2%) 45.6(-21.2%) Example D3 Type 9, 300-400 mPa·s 88.6 88.0(-0.7%) 31.5(-64.4%) Example D4 Type 9, 700-900 mPa·s 110.4 112.4(+1.8%) 45.1(-59.1%) Example D5 Type 6, 1000-2000 mPa·s 106.1 107.3(+1.1%) 40.3(-62.0%) Example D6 Type 9, 1000-2000 mPa·s 101.1 100.1(-1.0%) 48.0(-52.5%) Example A1 Type 9, 3000-4000 mPa·s 132.8 132.6(-0.2%) 47.5(-64.2%) Example D8 Type 6, 5000-7000 mPa·s 73.4 74.8(+1.9%) 113.3(+54.4%) Example D9 Type 9, 10000-15000 mPa·s 48.0 46.6(-2.9%) 99.3(+106.9%)

[0187] Examples A1, D1-D8 show that sodium carboxymethyl cellulose in various viscosity ranges can form ion cross-linked polymers with sodium alginate and calcium citrate. Among them, sodium carboxymethyl cellulose in the viscosity range of 5000-7000 mPa·s and 10000-15000 mPa·s still maintains ion cross-linking in simulated intestinal fluid at pH=6.8, and the liquid absorption multiple is greatly improved, while the product obtained from carboxymethyl cellulose in the viscosity range of 50-4000 mPa·s has good degradability in simulated intestinal fluid at pH=6.8, so the latter is more preferably used for the preparation of food-grade superabsorbent calcium supplement particles and applied to different types of products that provide a strong sense of satiety.

[0188] Group 5: Using sodium alginate with different viscosities

[0189] Examples E1-E3

[0190] 80 parts by mass of sodium carboxymethyl cellulose (viscosity 3000-4000 mPa·s), 20 parts by mass of sodium alginate, 1 part by mass of calcium citrate tetrahydrate containing calcium ions and 4900 parts by mass of deionized water were dispersed until uniform and transparent; the mixed solution was air-dried at 70° C. in a PP food contact plastic container for 24 hours; and 0.4-1 mm component particles were crushed and sieved for subsequent swelling performance testing.

[0191] Table 5 lists the liquid absorption multiples of the particles obtained in Examples A1, E1-E3 in 1 / 10 diluted simulated gastric fluid (pH=2.5) and simulated small intestinal fluid (pH=6.8):

[0192] Table 5

[0193] Example No. Sodium Alginate Parameters pH=2.51h pH=2.54h pH=6.81h Example E1 20-200mPa·s 95.7 98.9(+3.3%) 56.5(-41.0%) Example E2 200-300mPa·s 108.3 116.9(+7.9%) 56.4(-47.9%) Example A1 750-850mPa·s 132.8 132.6(-0.2%) 47.5(-64.2%) Embodiment E3 1000-1200mPa·s 103.1 109.9(+6.6%) 56.4(-45.3%)

[0194] Examples A1, E1-E3 show that commercially available sodium alginate of various viscosity ranges can be used to prepare ion cross-linked polymers, and have good dissociation performance in simulated intestinal fluid at pH = 6.8. Accordingly, commercially available food-grade raw materials can also be used to prepare food-grade super-absorbent calcium supplement particles and apply different types of products that provide strong satiety.

[0195] Group 6: Using different proportions and contents of sodium alginate and calcium citrate

[0196] Examples F1-F22

[0197] A total of 100 parts by mass of sodium carboxymethyl cellulose (viscosity 3000-4000 mPa·s) and sodium alginate (viscosity 750-850 mPa·s) and a certain amount of calcium citrate tetrahydrate were dispersed in 4900 parts by mass of deionized water until uniform and transparent; the mixed solution was air-dried at 70° C. in a PP food contact plastic container for 24 hours; and 0.4-1 mm component particles were crushed and sieved for subsequent swelling performance testing.

[0198] Table 6 lists the liquid absorption multiples of the particles obtained in Examples A1, F1-F22 in 1 / 10 diluted simulated gastric fluid (pH=2.5) and simulated small intestinal fluid (pH=6.8):

[0199] Table 6

[0200]

[0201]

[0202] *Mass ratio of raw materials: sodium carboxymethyl cellulose / sodium alginate / calcium ion (sodium alginate / calcium ion)

[0203] Examples A1 and F1-F22 show that when the mass ratio of sodium alginate to calcium ions is in the range of 60:1-5:2, it can form ion cross-linked polymers with sodium carboxymethyl cellulose; in particular, when the mass ratio of sodium carboxymethyl cellulose to sodium alginate is in the range of 3:2-9:1 and the mass ratio of sodium alginate to calcium ions is in the range of 20:1-10:1, the obtained ion polymer has a liquid absorption multiple of not less than 60 times in 1 / 10 simulated gastric juice at pH = 2.5, and the liquid absorption multiple changes after swelling for 1 hour and 4 hours are less than ±10%, which is more suitable for the preparation of food-grade super-absorbent calcium supplement particles and for application in different types of products.

[0204] Group 7: The role of anionic crosslinkers

[0205] Comparative Examples Z1, Z2

[0206] 100 parts by mass of sodium carboxymethyl cellulose (viscosity 3000-4000 mPa·s) and calcium citrate tetrahydrate containing 1 or 2 parts by mass of calcium ions are dispersed in 4900 parts by mass of deionized water until uniform and transparent; the mixed solution is dried in a PP plastic container at 70° C. until the moisture content is less than 10%; and 0.4-1 mm component particles are crushed and sieved for subsequent swelling performance testing.

[0207] Table 7 lists the liquid absorption multiples of the particles obtained in Examples A1, F16, Z1, and Z2 in 1 / 10 diluted simulated gastric fluid (pH=2.5) and simulated small intestinal fluid (pH=6.8):

[0208] Table 7

[0209] Example No. Raw material mass ratio* pH=2.51h pH=2.52h pH=2.53h pH=2.54h Example A1 80 / 20 / 1 132.8 124.5(-6.3%) 129.2(-2.7%) 132.6(-0.2%) Comparative Example Z1 100 / 0 / 1 102.4 148.0(44.5%) 149.4(45.9%) 153.3(49.7%) Example F16 80 / 20 / 2 116.0 116.2(0.2%) 118.8(2.4%) 117.4(1.2%) Comparative Example Z2 100 / 0 / 2 102.4 115.1(12.4%) 140.1(36.8%) 145.7(42.3%)

[0210] *Mass ratio of raw materials: sodium carboxymethyl cellulose / sodium alginate / calcium ion

[0211] Comparative Examples Z1 and Z2 show that if only calcium citrate is used for crosslinking without any anionic crosslinking agent, it takes 2 hours or more for the ion crosslinked polymer to reach swelling equilibrium, which is not conducive to controlling the swelling of the ion crosslinked polymer particles in the digestive tract.

[0212] Group 8: Use of other non-crosslinking additives

[0213] Embodiment G1, G2

[0214] 80 parts by weight of sodium carboxymethyl cellulose (viscosity 3000-4000 mPa·s), 20 parts by weight of sodium alginate (viscosity 750-850 mPa·s), 1 part by weight of calcium citrate tetrahydrate containing calcium ions, and 18 parts by weight of non-crosslinking additives were dispersed in 4900 parts by weight of deionized water until uniform and transparent; the mixed solution was dried in a PP plastic container at 70° C. until the moisture content was less than 10%; and 0.4-1 mm component particles were crushed and sieved for subsequent swelling performance testing.

[0215] Table 8 lists the liquid absorption multiples of the particles obtained in Examples G1 and G2 in 1 / 10 diluted simulated gastric fluid (pH=2.5):

[0216] Table 8

[0217]

[0218] Examples G1 and G2 show that the addition of non-crosslinking additives does not affect the crosslinking of ionomers in 1 / 10 simulated gastric fluid at pH = 2.5.

[0219] Group 9: Different concentrations and different drying conditions

[0220] Examples H1-H6

[0221] 80 parts by weight of sodium carboxymethyl cellulose (viscosity 3000-4000 mPa·s), 20 parts by weight of sodium alginate (viscosity 750-850 mPa·s), and 1 part by weight of calcium citrate tetrahydrate containing calcium ions are dispersed in a certain amount of drinking water until they are uniform and transparent; the mixed solution is air-dried in a PP plastic container until the moisture content is less than 10%; and 0.4-1 mm component particles are crushed and sieved for subsequent swelling performance testing.

[0222] Table 9 lists the liquid absorption multiples of the particles obtained in Examples A1, H1-H6 in 1 / 10 diluted simulated gastric fluid (pH=2.5) and simulated small intestinal fluid (pH=6.8):

[0223] Table 9

[0224] Example No. concentration Drying temperature pH=2.51h pH=2.54h pH=6.81h H1 2% 50℃ 79.8 81.0(+1.2%) 34.1(-57.3%) A1 2% 70℃ 132.8 132.6(-0.2%) 47.5(-64.2%) H2 4% 80℃ 123.9 119.2(-3.8%) 84.5(-31.8%) H3 4% 105℃ 121.6 117.1(-3.7%) 69.3(-43.0%) H4 5% 70℃ 99.7 97.5(-2.2%) 55.3(-44.5%) H5 5% 80℃ 87.9 83.1(-5.5%) 37.1(-57.8%) H6 5% 105℃ 80.2 81.2(+1.2%) 48.4(-39.7%)

[0225] Examples G1-8 show that although the mixing concentration and drying temperature have a slight influence on the swelling properties of the ionomer, the ionomer of the present invention can be obtained. The appropriate mixing concentration and drying temperature can be selected according to actual needs.

[0226] Large-scale preparation

[0227] 0.4kg sodium carboxymethyl cellulose (viscosity 3000-4000mPa·s), 0.1kg sodium alginate (viscosity 750-850mPa·s) and 2.5kg drinking purified water were mixed for 0.5 hours to obtain fully water-absorbing micelles. 3kg micelles, 7kg drinking purified water and 23.7g calcium citrate tetrahydrate were dispersed in a 50L mixing reactor at 200rpm for 2.5 hours to obtain a uniform and transparent water mixture. The mixture was divided into six portions and spread flat on metal plates covered with anti-stick cloth with a thickness of about 2cm, and dried at 80℃ until the moisture content was less than 10%; crushed on the plate and sieved to obtain 0.4-1mm component particles for subsequent swelling performance tests. The results are shown in Table 10:

[0228] Table 10

[0229]

[0230] The above results show that the performance of the ionomer and particles obtained at the 10 kg scale is not much different from that of the small-scale samples, and the uniformity is good. In particular, the mixing process including premixing only takes 3 hours in total, which greatly improves the mixing efficiency.

[0231] Study on satiety and water retention

[0232] In order to understand the absorption and retention of liquid by the particles in the human digestive tract, the following study was conducted.

[0233] The three subjects were asked to fast and drink no water 3 hours before meals, and drink (1) solid beverages and drinking water 0.5 hours before meals, with a total of 400 mL of drinking water; or (2) only drink 400 mL of drinking water. Each person's meal consisted of half a portion of rice (relative to each subject's daily food intake), one portion of meat, two portions of vegetables, and one portion of soup (about 250 mL). After meals, they were asked to fast and drink no water until the end of this round of research. After drinking water, the time and frequency of urination were recorded and the feeling of fullness was asked. Two rounds were conducted in total.

[0234] Among them, the screening principles for subjects are: fasting and no drinking water for 3 hours before meals, drinking 400mL of drinking water 0.5 hours before meals, eating normally, and urinating 3 times or more within 2.5 hours after drinking water.

[0235] The solid beverage components are as follows:

[0236] Food-grade super-absorbent calcium supplement particles 0.4-1 mm (prepared according to the large-scale preparation protocol of the previous example), 2.5 g;

[0237] Hydrolyzed collagen, 1g;

[0238] White Kidney Bean Extract, 1g

[0239] Citric acid, 45 mg;

[0240] Neotame, 5 mg;

[0241] Natural fruit powder, 0.8g.

[0242] Table 11

[0243]

[0244] Note: √ = feeling full or not hungry; × = feeling hungry

[0245] From the time period when the subjects urinated relatively concentratedly in Table 11, it can be concluded that the particles retain the liquid in the digestive tract for about 3-4 hours, after which the particles dissociate and release water, which is reflected in the increase in the frequency of urination. Accordingly, the particles can better prolong the feeling of fullness and delay the feeling of hunger.

[0246] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. An ion cross-linked polymer, characterized in that It contains at least a composite cross-linking agent and a water-soluble polymer with a carboxyl group or its sodium salt on the side group. The composite cross-linking agent is formed by compounding a calcium salt and an anionic cross-linking agent with a carboxyl group or its sodium salt on the side group. The calcium salt is a slightly soluble calcium salt or a calcium salt composition containing the calcium salt. The ion cross-linking polymer is cross-linked by the physical action between calcium ions and carboxyl groups, and no chemical reaction occurs between the raw materials.

2. An ion cross-linked polymer according to claim 1, characterized in that: The calcium salt is a slightly soluble organic calcium salt or a calcium salt composition containing the same; the anionic crosslinking agent is selected from sodium alginate, linseed gum, low-ester pectin and combinations thereof; the water-soluble polymer having a carboxyl group or its sodium salt on the side group contains at least 0.5 carboxyl groups per repeating unit on average, and is selected from acrylic acid homopolymers and copolymers thereof, sodium acrylate homopolymers and copolymers thereof, polysaccharide polymers having a carboxyl group or its sodium salt on the side group and combinations thereof; the mass ratio of the water-soluble polymer to the anionic crosslinking agent is 1:1-9:1, and the mass ratio of the anionic crosslinking agent to the calcium ion is 60:1-5:2; the molar ratio of the total negative charge of the acid radical ion of the slightly soluble organic calcium salt to the total positive charge of the calcium ion is 9:20-21:

20.

3. An ion cross-linked polymer according to claim 1, characterized in that: The calcium salt is selected from calcium citrate, a combination of calcium citrate and calcium malate, a combination of calcium citrate and a water-soluble calcium salt, and a combination of a water-soluble citrate and a water-soluble calcium salt; the water-soluble citrate is selected from sodium citrate, potassium citrate and a combination thereof, and the water-soluble calcium salt is selected from calcium lactate, calcium gluconate, calcium ascorbate and a combination thereof; the anionic crosslinking agent is selected from sodium alginate; the water-soluble polymer having a carboxyl group or a sodium salt thereof as a side group is selected from sodium carboxymethyl cellulose, and a 1% aqueous solution prepared from the sodium carboxymethyl cellulose has a viscosity of 50-4000 mPa·s at 25°C; the degree of substitution of the sodium carboxymethyl cellulose is not less than 0.5; the mass ratio of the sodium carboxymethyl cellulose to the sodium alginate is 1:1-9:1, and the mass ratio of the sodium alginate to the calcium ion is 60:1-5:2; the molar ratio of the citrate to the calcium ion is 3:10-7:

10.

4. A food-grade super-absorbent calcium supplement granule, characterized in that: The food-grade super-absorbent calcium supplement particles contain an ion cross-linked polymer, which contains at least a composite cross-linking agent and a water-soluble polymer containing a carboxyl group or its sodium salt on the side group, wherein the composite cross-linking agent is a composite of a calcium salt and an anionic cross-linking agent containing a carboxyl group or its sodium salt on the side group; the ion cross-linked polymer is cross-linked by the physical action between calcium ions and carboxyl groups, and no chemical reaction occurs between the raw materials; Wherein, the calcium salt is selected from calcium citrate, a combination of calcium citrate and calcium malate, a combination of calcium citrate and a water-soluble calcium salt, a combination of a water-soluble citrate and a water-soluble calcium salt, wherein the water-soluble citrate is selected from sodium citrate, potassium citrate and a combination thereof, and the water-soluble calcium salt is selected from calcium lactate, calcium gluconate, calcium ascorbate and a combination thereof; the anionic crosslinking agent is selected from sodium alginate; the water-soluble polymer having a carboxyl group or its sodium salt on the side group is selected from sodium carboxymethyl cellulose, and the viscosity of a 1% aqueous solution prepared from the sodium carboxymethyl cellulose at 25° C. is 50-4000 mPa·s; the sodium carboxymethyl cellulose is type 6 or type 9; Wherein, the mass ratio of sodium carboxymethyl cellulose to sodium alginate is 3:2-9:1, the mass ratio of sodium alginate to calcium ions is 20:1-10:1; the molar ratio of citrate to calcium ions is 3:10-7:10; The food-grade super-absorbent calcium supplement particles may or may not contain other food additives and do not contain cross-linking agents that form chemical cross-links with any raw materials; The food-grade super-absorbent calcium supplement particles have a liquid absorption multiple of not less than 50 times after swelling for 1-4 hours in a 1 / 10 diluted simulated gastric juice at pH = 2.5, and the liquid absorption multiple after swelling for 4 hours varies by no more than ±25% compared with the liquid absorption multiple after swelling for 1 hour; the liquid absorption multiple of the swollen residue after swelling for 1 hour in simulated small intestinal fluid is not higher than 80% of the liquid absorption multiple after swelling for 1 hour in a 1 / 10 diluted simulated gastric juice at pH = 2.

5.

5. The food-grade super-absorbent calcium supplement granules according to claim 4, characterized in that: The liquid absorption multiple of the food-grade super-absorbent calcium supplement particles after swelling in 1 / 10 simulated gastric fluid for 4 hours varies by no more than ±10% compared with the liquid absorption multiple after swelling for 1 hour, and the liquid absorption multiple of the swollen residue after swelling in simulated small intestinal fluid for 1 hour is no higher than 70% of the liquid absorption multiple after swelling in 1 / 10 diluted simulated gastric fluid at pH = 2.5 for 1 hour.

6. The food-grade super-absorbent calcium supplement granules according to claim 4, characterized in that: The particle size of the food-grade super-absorbent calcium supplement particles is 0.1-1 mm.

7. The food-grade super-absorbent calcium supplement granules according to claim 4, characterized in that: The method for preparing the food-grade super-absorbent calcium supplement granules comprises at least the following steps: S1. Mixing the raw materials with water until they are completely dispersed and uniformly dispersed to obtain a water mixture; wherein the sum of the mass of sodium carboxymethyl cellulose and sodium alginate is not more than 5% of the total mass; S2. Transfer the water mixture to a non-stick container; S3. Drying the aqueous mixture at a temperature of 50-105 ° C to obtain a solid composite; S4. The obtained solid composite is crushed and sieved to obtain the food-grade super-absorbent calcium supplement particles; The water is drinking purified water or drinking deionized water.

8. The food-grade super-absorbent calcium supplement granules according to claim 4, characterized in that: The method for preparing the food-grade super-absorbent calcium supplement particles further comprises the following premixing step S0 before the step S1: S0. Mix sodium carboxymethyl cellulose, sodium alginate and drinking water to obtain micelles; wherein the sum of the mass of sodium carboxymethyl cellulose and sodium alginate accounts for 15-20% of the total mass of the micelles.

9. A product that provides a feeling of fullness, characterized in that The product contains 0.1-99.9% by mass of food-grade super-absorbent calcium supplement particles as described in claims 4-8.

10. The product for providing satiety according to claim 9, characterized in that: The product is food, medicine or medical device; the food is in the form of solid beverage, candy, pet food; the medicine or medical device is in the form of tablets, capsules, and granules.

Citation Information

Patent Citations

  • Methods and compositions for weight management and for improving glycemic control

    CN105815363A

  • A composition for weight loss

    CN110496135B

  • Improved superabsorbent materials and methods of production thereof

    CN110740759A

  • A hydrogel for assisting in diet control, its preparation method and application

    CN112262984B

  • Chitosan hydrogel, preparation method and application of chitosan hydrogel in gastric filling agent

    CN113519851A